A Mini-Review on the Chemical Constituents and Biological Activities of Lysimachia capillipes Hemsl. - Jiang, Fujunrui; Yong, Jianping; Lu, Shaoji; Huang, Ruiwen; Tian, Danian; Lu, Canzhong (Current Traditional Medicine, 2024)
Lysimachia capillipes Hemsl. is an annual flowering plant, mainly distributed in some parts of Asia. In the early 1970s, it was discovered by the folk of Le'an county, Jiangxi province. Lysimachia capillipes Hemsl., contains many bioactive components (flavonoids, saponins, volatile oils, organic acids, etc.) and has a wide spectrum of pharmacological activities. This plant medicine was used in the treatment of cold cough, asthma, rheumatism, pain, irregular menstruation, neurasthenia, restoring deficiency, expelling roundworm, anti-tumor, etc. in Chinese folk. In this minireview, the progress on the chemical constituents and biological activities of Lysimachia capillipes Hemsl., was comprehensively summarized by searching the CNKI, PubMed, Web of Science, Scopus, and Google Scholar databases using
Keywords: saponins